Persepsi Masyarakat Desa Tambe Kecamatan Bolo Kabupaten Bima Terhadap Desain Masjid - Mursalin; Arif Rahman (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Bima, 2023)
This study aims to reveal the perceptions of the people of Tambe village, Bolo district, Bima district about the mosque design (a study of Qs. al-Taubah/9: 107-108).This type of research is qualitative and is presented descriptively. This research took place from September to February 2023. The primary data sources in this study were religious leaders, religious instructors, youth leaders, and the general public. Secondary data includes books, magazines, newspapers, television, radio and other relevant written works. Data collection methods include observation and interviews. The research instruments used were cameras, voice recorders, pens, notebooks. Data analysis was carried out by means of data condensation, data presentation, and drawing conclusions. Whereas the people of Tambe village, Bolo sub-district, Bima district, generally disagree with the design of a mosque that resembles a building or place of worship of another religion, although there are some who argue that there are pros and cons in social media, none of the interview researchers agreed with mosque design that resembles other religious buildings. In the Qur'an, there is no specific explanation that discusses the design of the mosque specifically, but there are verses that explain the dhirar mosque, namely QS. al-Taubah/9:107–108. It can be concluded from the interpretation of these verses that the dhirar mosque is interpreted as a mosque established with the intention of endangering or causing harm to the Muslims. The verse does not provide a specific explanation about the shape of the mosque, but the mosque is quite clean and faces the Qibla. So that people feel comfortable in worshiping or worshiping their god.